Positive childhood experiences can moderate the impact of adverse childhood experiences on adolescent depression and anxiety: Results from a cross-sectional survey. (March 2022) - Qu, Guangbo; Ma, Shaodi; Liu, Haixia; Han, Tiantian; Zhang, Huimei; Ding, Xiuxiu; Sun, Liang; Qin, Qirong; Chen, Mingchun; Sun, Yehuan
Abstract: Background: Adverse childhood experiences (ACEs) are common and have a wide range of impact on human physical and mental health. The role of positive childhood experiences (PCEs) and its interaction with ACEs on adolescent depression and anxiety are less known. Methods: A cross-sectional survey on Chinese primary and secondary school students was conducted to investigate information of ACEs, PCEs, depression, anxiety and demographic characteristics ( n  = 6363). Logistic regression analyses were performed to evaluate the association between specific types and cumulative of PCEs and ACEs and risk of depression, anxiety and its comorbidity. Interaction analyses were conducted to determine the moderation role of PCEs on the impact of ACEs. Results: ACEs were positively correlated with the risk of depression and anxiety and there was a significant positive does-response relationship between cumulative ACEs exposure and risk of depression, anxiety and its comorbidity. PCEs were negatively associated with the risk of depression and anxiety and there was an inverse does-response relationship between cumulative PCEs exposure and risk of depression. Adolescents with low ACEs (<4 counts) and high PCEs (6–7 counts) exposure showed significant lower risk of depression and there were negative additive interactions between PCEs and ACEs exposure on risk of depression and the comorbidity of depression and anxiety. Conclusions: PCEs can moderate the impact of ACEs on mental health of adolescents. Early and proactively promoting PCEs contributes to promoting well-being, especially for adolescents with ACEs.